The effects of tawhidic paradigm paradigm on social entrepreneurship education - Mhd. Sarif, Suhaimi; Sarwar, Abdullah Al-Mamun (2014)
This paper argues Tawhidic paradigm has significant effects on social entrepreneurship education in the Muslim world. The basis for Tawhidic paradigm is adherence to the Qur'an and the Sunnah, which is reflecting in faith (Tawhid), worship (ibadah), and ethics (akhlaq) and manifestation of human as servant and vicegerent of Allah. Social entrepreneurship is about doing business for the benefits of the community. While social entrepreneurship emphasized on well being, welfare and wellness of human being at large, the discipline has serious deficiency to sustain the social entrepreneurship to be really social welfare driven. Thus, this study argues that Tawhidic paradigm provides a contingency perspective on the social entrepreneurship education. Being a conceptual one, this study heavily relied on the secondary data which had been collected from both online and printed sources. The preliminary findings show that while Islam is the dominant religion in Malaysia, the education system mostly practices conventional educational philosophy. However, the informants argued that Tawhidic paradigm has effect on individual’s religiosity and spirituality. The study suggests future research to include policy makers and entrepreneurship associations’ representatives.